Autocratic Consent to International Law: The Case of the International Criminal Court's Jurisdiction, 1998–2017. (2020) - Hashimoto, Barry
Abstract: This article contributes to an understanding of why autocrats have accepted the jurisdiction of the International Criminal Court. Leveraging their ability to obstruct their own prosecution, autocrats have traded off the risk of unwanted prosecutions against the deterrent threat that prosecutions pose to political rivals and patrons of their enemies conspiring to oust them. The risk of unwanted prosecutions and the court's deterrent threat both arise because ICC prosecutions credibly communicate guilt for international crimes to capital-disbursing democracies, which may, insofar as possible, use leader-specific economic statecraft to prevent the administration of foreign states by those whom the court signals are guilty of international crimes. Analysis using fixed effects and matching shows that a greater reliance on capital publicly financed by democracies increased the probability that a state accepted the court's jurisdiction only when it was an autocracy (1998–2017). ICC jurisdiction also lengthened the tenure of autocrats and reduced the severity of civil conflict in autocracies.